Combining serum inflammatory markers and clinical factors to predict survival in metastatic urothelial carcinoma patients treated with immune checkpoint inhibitors - Liang-Yun Cheng; Po-Jung Su; Ming-Chun Kuo; Chang-Ting Lin; Hao-Lun Luo; Chih-Chi Chou; Shih-Yu Huang; Chia-Che Wu; Chien-Hsu Chen; Chun-Chieh Huang; Kai-Lung Tsai; Harvey Yu-Li Su (Therapeutic Advances in Medical Oncology)
Background: Despite the revolutionary impact of immune checkpoint inhibitors (ICIs) on the treatment of metastatic urothelial carcinoma (mUC), the clinical utility of reliable prognostic biomarkers to foresee survival outcomes remains underexplored. Objectives: The purpose of this study was to ascertain the prognostic significance of serum inflammatory markers in mUC patients undergoing ICI therapy. Design: This is a retrospective, multicenter study. Methods: Data were collected from two independent medical centers in Taiwan, encompassing a validation and a training cohort (TC). Patients with histopathologically confirmed urothelial carcinoma who received at least one cycle of ICI monotherapy were included. Serum inflammatory markers such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) were calculated prior to ICI therapy. Statistical analyses involved the use of receiver operating characteristic (ROC) curves to determine optimal biomarker cutoffs and Cox proportional hazards models to evaluate the independent predictive capability of these markers. Results: A total of 192 patients were enrolled. In the univariate analysis, serum markers such as NLR, PLR, SII, and Hb were significantly associated with overall survival (OS) in both the training and validation cohorts (VC). White blood cells, NLR, and SII demonstrated a robust correlation with progression-free survival across both cohorts. Multivariate analysis revealed that Eastern Cooperative Oncology Group performance status ⩾2 ( p  < 0.001), visceral metastasis ( p  < 0.001), leukocytosis ( p  < 0.001), Hb levels ⩾10 mg/dL ( p  = 0.008), and NLR ⩾5 ( p  = 0.032) as independent predictors of OS. A prognostic nomogram integrating these independent factors yielded a C-index for a 3-year OS of 0.769 in the TC and 0.657 in the VC. Conclusion: Serum inflammatory markers, combined with clinicopathologic factors, provide a practical prognostic tool in mUC treatment with ICIs.